Automated manufacturing systems actuators, controls, sensors, and robotics - Morriss, S. Brian (Glencole McGraw-Hill, 1994)
This introductory text examines the components used in automated systems. It provides coverage of sensors, actuators, controllers and control theory, and discusses some special-purpose automation components, automation systems and automation concepts.